Protection Of Healthcare Workers’ Rights To Refuse The Covid-19 Vaccination In Kebumen District - Rachmadi, Triyo (Universitas Islam Indonesia, 2021)
The government’s policy in implementing the nation-wide mandatory COVID-19 vaccination program aims to reduce the risk of transmission of the COVID-19 disease. However, some healthcare workers do not believe that the vaccination is effective. Every citizen has the right to refuse vaccination against COVID-19, including the healthcare workers. The research questions are (1) how the protection of the healthcare workers’ right to refuse the COVID-19 vaccination in Kebumen District? (2) How does the legal theory address the problem of the right to refuse the COVID-19 vaccine? This research uses sociological or empirical non-doctrinal methods with a qualitative descriptive approach, the research was conducted in Kebumen District with bureaucrat, healthcare workers and head of the healthcare professional organization as the respondents. Theories used in this research are ethics and human rights, work of law in society hegemony and domination. The results show that the rights of healthcare workers too refuse the COVID-19 vaccination is not guaranteed and protected by the government. Healthcare workers who refuse vaccination sanctioned. The government and the healthcare workers have the same interests; hence a consensus is needed in the form of a hegemony and domination which is mutually beneficial and not detrimental to both parties.Keywords: Healthcare workers; refusal; rights; vaccinePerlindungan Hak Tenaga Kesehatan untuk Menolak Vaksinasi Covid-19 di Kabupaten KebumenAbstrakKebijakan pemerintah dalam melaksanakan program vaksinasi wajib COVID-19 secara nasional bertujuan untuk mengurangi risiko penularan penyakit COVID-19. Namun, beberapa petugas kesehatan tidak percaya bahwa vaksinasi itu efektif. Setiap warga negara berhak menolak vaksinasi terhadap COVID-19, termasuk tenaga kesehatan. Rumusan Masalah yang disajikan adalah (1) bagaimana perlindungan hak tenaga kesehatan untuk menolak vaksinasi COVID-19 di Kabupaten Kebumen? (2) Bagaimana teori hukum menyikapi masalah hak menolak vaksin COVID-19? Penelitian ini menggunakan metode non-doktrinal sosiologis atau empiris dengan pendekatan deskriptif kualitatif, penelitian ini dilakukan di Kabupaten Kebumen dengan responden birokrat, petugas kesehatan dan pimpinan organisasi profesi kesehatan. Teori yang digunakan dalam penelitian ini adalah etika dan hak asasi manusia, kerja hukum dalam hegemoni dan dominasi masyarakat. Hasil penelitian menunjukkan bahwa hak tenaga kesehatan juga menolak vaksinasi COVID-19 tidak dijamin dan dilindungi oleh pemerintah. Petugas kesehatan yang menolak vaksinasi diberi sanksi. Pemerintah dan petugas kesehatan memiliki kepentingan yang sama; maka diperlukan konsensus berupa hegemoni dan dominasi yang saling menguntungkan dan tidak merugikan kedua belah pihak.Kata Kunci: Petugas kesehatan; penolakan; hak; vaksin